2010
DOI: 10.1007/s00330-010-1961-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the coronary venous system in heart failure patients by blood pool agent enhanced whole-heart MRI

Abstract: Contrast-enhanced MRI venography appears feasible for non-invasive pre-interventional assessment of the course of the CS and its major tributaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This limits the accessibility of the anterolateral, lateral and posterolateral LV regions. The averaged branch positions in our examination are largely in line with those in previous studies (41,47,48).…”
Section: Significance Of the Coronary Vein Morphology In Crtsupporting
confidence: 91%
“…This limits the accessibility of the anterolateral, lateral and posterolateral LV regions. The averaged branch positions in our examination are largely in line with those in previous studies (41,47,48).…”
Section: Significance Of the Coronary Vein Morphology In Crtsupporting
confidence: 91%
“…Previous studies have used magnetic resonance (MR) 4 and CT 5-12 imaging on live patients to assess the anatomies of the cardiac venous system. The main advantage of our study is that there is no danger to live patients due to contrast injection and radiation exposure [13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…New imaging methods can be useful in finding an explanation for this phenomenon [5]. There have been several studies which have confirmed the usefulness of MSCT for the visualization of the coronary venous system, but none of them included patients with a previous bypass grafts implantation [6, 7].…”
Section: Introductionmentioning
confidence: 99%